Brief Report: Integrating Social-Emotional Learning with Literacy Instruction: An Intervention for Children at Risk for Emotional and Behavioral Disorders. (November 2013) - Daunic, Ann; Corbett, Nancy; Smith, Stephen; Barnes, Tia; Santiago-Poventud, Lourdes; Chalfant, Pam; Pitts, Donna; Gleaton, Jeisha
It is widely believed that children's social-emotional growth and academic learning are inextricably connected. Pressured by high-stakes assessments, however, school professionals find it difficult to devote adequate time to children's social/behavioral development. As a response, we developed and piloted Social-Emotional Learning Foundations (SELF), a curriculum for students at risk for emotional or behavioral problems that merges instruction in social-emotional learning with early literacy skills. Designed for small-group instruction, the SELF curriculum provides teachers multiple opportunities to extend language and promote emotional and behavioral self-regulation while teaching early literacy skills that include vocabulary development and comprehension. This preliminary study was used to explore intervention feasibility, pilot implementation, and measurement protocols and to provide some evidence in support of further study. Findings from the pilot implementation in eight kindergarten classrooms indicated that SELF lessons improved teacher-reported executive function, internalizing behavior, and school-related competence. As a preface to a more rigorously designed efficacy study, the pilot study results provide preliminary evidence that integrating social-emotional learning and literacy instruction may be a viable strategy for promoting self-regulation in the service of positive social and academic outcomes for children at risk.